Advanced transcoding techniques for video communication - Shu, Haiyan (2008)
Video transcoding is an efficient tool for video adaptation to provide seamless service for end users. In this works, three transcoding schemes are discussed to enhance the output video quality. Downsizing transcoding was the first main concern. The resizing algorithms were discussed first. Two resizing algorithms were proposed to realize arbitrary downsizing in the DCT domain directly. Then, frame size selection problem was solved by the proposed scheme. Next, frame skipping transcoding was discussed. In this work, the concept of ``motion change'' was introduced to evaluate the motion continuity. Combined with the motion activity information, these two parts of information were used to determine the skipping pattern of the transcoded bitstream. The nonlinear motion in the transcoded bitstream is reduced. Last, error resilient transcoding was investigated. Based on the conventional rate-distortion optimized intra refresh scheme, an enhanced intra/inter macroblock mode decision scheme was proposed, which considers not only the error propagated from previous frames, but also the error propagated to the next frame.